The Use of Antibiotics at the End of Life: A Cross-Sectional Study - Brayan Miranda-Chavez; Andre Fuentes-Yufra; Miguel Hueda-Zavaleta; Cesar Copaja-Corzo; Javier A. Flores-Cohaila; Marco Rivarola-Hidalgo (SAGE Publishing, 2024)
Objective: To identify and analyze antibiotics' prescription patterns and associated factors among terminally ill patients at a hospital in southern Peru. Methodology: A cross-sectional analytical study was conducted on adult patients who died in Hospital III Daniel Alcides Carrion in Tacna, Peru, 2023. Data were collected from electronic medical records, focusing on antibiotic use during the last hospitalization. Univariate, bivariate, and multivariate analyses were performed using Poisson regression to adjust for potential confounders. Results: The study included 239 patients with an average age of 76. Antibiotics were administered to 93.72% of patients, with 42.46% lacking an identified infectious focus. Ceftriaxone, Meropenem, and Vancomycin were the most used antibiotics. A lower use of antibiotics within 72 hours prior to death was associated with hospitalizations longer than 18 days and having 2 or more comorbidities. Conclusion: The high prevalence of antibiotic use at the end of life, often without an infectious focus, suggests a need for better guidelines and education on palliative care to avoid inappropriate antibiotic prescribing. Improved communication between healthcare providers, patients, and families is essential for optimizing end-of-life care.